1992
DOI: 10.1139/b92-239
|View full text |Cite
|
Sign up to set email alerts
|

Light-growth response relationships in Pacific silver fir (Abies amabilis) and subalpine fir (Abies lasiocarpd)

Abstract: Pacific silver fir and subalpine fir, both typically inhabiting high-elevation forests in northwestern North America, were considered shade-tolerant species, the former more tolerant than the latter. To determine their relative shade tolerance, established advance regeneration was sampled along a light gradient ranging from open areas to inside a forest stand, and analysis of irradiance, growth, and leaf measures was obtained. Relationships between the percentage of above-canopy light (in the photosyntheticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
57
1
7

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 17 publications
13
57
1
7
Order By: Relevance
“…This seems to suggest that our six-year-old planted saplings were not heavily suppressed by the light gradient found in the understory. Similar effects of a light gradient on growth in situ have been reported for more shade-tolerant conifers (Klinka et al 1992, Parent and Messier 1995, Chen et al 1996. However, shade-tolerant conifers tended to reach maximum growth at lower light levels of approximately 25% PPFD and to have a much reduced height growth at low light levels.…”
Section: Height and Diameter Growthsupporting
confidence: 75%
“…This seems to suggest that our six-year-old planted saplings were not heavily suppressed by the light gradient found in the understory. Similar effects of a light gradient on growth in situ have been reported for more shade-tolerant conifers (Klinka et al 1992, Parent and Messier 1995, Chen et al 1996. However, shade-tolerant conifers tended to reach maximum growth at lower light levels of approximately 25% PPFD and to have a much reduced height growth at low light levels.…”
Section: Height and Diameter Growthsupporting
confidence: 75%
“…These results are consistent with other studies from several coastal sites in British Columbia that found the maximum growth potential for amabilis fir and western hemlock occurs when canopy light transmittance is greater than 75% Klinka 1992, Klinka et al 1992) a level that occurred in less than half of the SW microsites (Beese et al 2004). Gaps in the dispersed SW were variable in size, most being under one tree height in diameter (approximately 0.1 ha), a gap size below which growth declines have been reported in both western hemlock and amabilis fir (Gray andSpies 1996, Coates 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Understory light availability is a good proxy for predicting juvenile tree growth in complex structured northern latitude forests (e.g., Klinka et al, 1992;Chen, 1997;Wright et al, 1998;Coates and Burton, 1999;Drever and Lertzman, 2001;Claveau et al, 2002). SORTIE/BC can predict light levels after any type of partial cutting, and it can be easily parameterized for different forest ecosystems (Canham et al, 1994(Canham et al, , 1999Beaudet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%